The Golden Horde through the eyes of Contemporaries and Eyewitnesses - Ivanov V.A. (Золотоордынское обозрение)
The purpose of the study: To show how the Golden Horde was seen – its population, its way of life, appearances, occupations – by representatives of the European (Catholic) and Eastern (Muslim) worlds. Their impressions, set out in the corresponding narratives, not only created the image of this state, but also influenced later ideas about the peoples who inhabited the eastern steppes – “Tartaria”. Research materials: The main source on the history of the Golden Horde/Ulus of Jochi are the narrative works of medieval European and Arab-Persian authors. Most eastern narrativist writers had never visited the territory of this state. They drew their information either from the stories of traveling merchants and envoys, or from the writings of their predecessors in compilations. In this regard, the narratives created by Europeans, from the point of view of source studies, differ favorably from the Arab-Persian ones not only in their information content, but also in the directness of its transmission. Research results and scientific novelty: Almost all the narratives known to us related to the Golden Horde were created for political purposes. Accordingly, their content reflects precisely the political, military and dynastic history of this state. Those few authors who had the opportunity to observe the life of the Golden Horde with their own eyes and from the inside – Plano Carpini, Guillaume (Willem) Rubruk, Marco Polo, Ibn Battuta – recorded approximately the same things in their notes, namely that “Tatars” were nomads who fed on the products of cattle breeding and hunting, were unpretentious in everyday life, unpretentious in clothing, formally Muslims but in fact dual-religionists since they preserved pagan remnant traditions of nomads. It is almost impossible to establish the scale of urbanization of the Golden Horde from these narratives. Thus, from the point of view of historical source study, the available material objectively forms three main empirical directions in the study of the Golden Horde, each of which has its own subject, without intersecting and practically without interacting with each other: the archeology of the Golden Horde nomads, the archeology of settlements (cities), and socio-political history. Therefore, the modern presentation of the history of the Golden Horde has the character of essays which will evidently persist for quite a long time.